PERAN GURU DALAM PENGENALAN MAKANAN BERGIZI SEIMBANG PADA ANAK USIA 5-6 - Yulina, Ika; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2023)
This study aims to describe the teacher's role in introducing balanced nutritious food to children aged 5-6 years at PGRI Karya Nilam Kindergarten, Ketapang Regency. The research method used is descriptive with a qualitative research form. The data source for this study was the B1 group teacher and the data consisted of observation sheets and the results of interviews with B1 group teachers as well as documentation of learning activities in class B1. The results of the study show: 1. The role as an inspiration in introducing balanced nutritious food, namely, the teacher sets an example and becomes a role model for children, for example, the teacher shows a good example to children with habituation, such as showing nutritious food supplies, showing types of balanced nutritious food, and shows people eating a nutritionally balanced diet; 2. The role of the teacher as a motivator in introducing balanced nutritious food to children, namely, providing encouragement and motivation to children so that children are always enthusiastic about learning, besides that the teacher also gives praise to children such as applause